2018
DOI: 10.1177/1352458518790390
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of therapy switch in multiple sclerosis treatment-naïve patients: A real-life study

Abstract: Several factors are associated with higher switch risk in patients starting a first-line therapy and could be integrated in the decision-making process of first treatment choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 28 publications
8
31
2
4
Order By: Relevance
“…Our casefinding algorithm has 99.0% sensitivity, and is applied on 10% of the Italian population [15]. Of note, our demographics and Interferon Beta prescription rates are in line with international studies conducted within the same time frame, on equally sized populations [26,[31][32][33][34], thus suggesting overall generalisability of current findings.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our casefinding algorithm has 99.0% sensitivity, and is applied on 10% of the Italian population [15]. Of note, our demographics and Interferon Beta prescription rates are in line with international studies conducted within the same time frame, on equally sized populations [26,[31][32][33][34], thus suggesting overall generalisability of current findings.…”
Section: Discussionsupporting
confidence: 75%
“…Reasons for Interferon Beta discontinuation are unfortunately not traceable in routinely-collected healthcare data, though possibly resulting from a combination of poor tolerance/side effects (accounting for up to 60% of discontinuation reasons), and lack of efficacy [23,24], and could be only derived from the switching pattern indirectly. For instance, in our cohort, lower persistence to Plegridy® could be attributed to poor tolerance and/or higher number of side effects, since most patients switched towards medications with similar efficacy profile (horizonal switch) [33], as also suggested in clinical studies [24,40].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Given the increasing availability of oral drugs for MS, namely once daily terilunomide (TFN) and twice daily dimethyl fumarate (DMF), a potential strategy to enhance adherence in the long term might be switching from an injective to an orally administered treatment [18][19][20]. Another potential strategy encompasses the reduction of IFNB administration frequency by switching to pegylated interferon (PEG) that is given every 2 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Details on the study design of the CLARITY data set can be found in the article reporting the clinical trial results, 3 and details about the i-MuST database collection can be found in previous publications. 5 This study takes advantage of the availability of the placebo arm of the CLARITY study, thus providing a reference to which each treatment can be compared.…”
Section: Methodsmentioning
confidence: 99%